Effect of pore-size distribution on unsaturated shear strength of residual soil from granitic Bukit Timah formation - Ang, Qimou (2009)
Singapore’s land comprises mostly residual soils. The residual soil from the Bukit Timah granitic formation is often found in an unsaturated condition. Soil-water characteristic curve (SWCC) of the soil shows how weathering grade has affected the pore-size distribution of the residual soil. The objective of the project is to investigate the effect of pore-size distribution on unsaturated shear strength of residual soil of the Bukit Timah granitic formation.